E-Commerce Purchase Intention Model with Consumer Reviews, Trust, and Risk as Predictors of Msmes Culinary Products - Suswita Roza; Ade Octavia; Sriayudha, Yayuk (Dinasti Publisher, 2022)
One of the efforts to increase the capacity of MSMEs, particularly on culinary products is by optimizing e-commerce-based technology through the marketplace platform. Previous research has found that internal consumer factors heavily influence consumer buying interest. For purchases using e-commerce, the elements of trust and acceptance of risk are essential, in addition to other factors, such as consumer perceptions based on social media. This study's main objective is to analyze the role and influence of consumer reviews, the risks received by consumers, and consumer trust on consumer purchase intentions. The research design uses a quantitative descriptive. The research sample consisted of 200 e-commerce consumers for culinary products in Jambi City. The sampling technique uses probability sampling with survey sampling using questionnaires, interviews, and observations. The analysis tool uses Structural Equation Modeling -PLS. the research results show a significant relationship between consumer reviews and consumer trust. Risk and consumer trust also affect purchase intensity. However, the study's results also show no significant effect between consumer reviews and purchase intentions, as well as consumer trust and the risk received. It is hoped that the research results will benefit many parties who need references, such as e-commerce users, business actors, and academics conducting research in the same field.